2007
DOI: 10.1007/s00192-007-0437-2
|View full text |Cite
|
Sign up to set email alerts
|

Related factors of urge, stress, mixed urinary incontinence and overactive bladder in reproductive age womenin Tabriz, Iran: a cross-sectional study

Abstract: Urinary incontinence remains a pressing problem, particularly for women. So this study was conducted to assess risk factors for stress, urge, mixed urinary incontinence and overactive bladder (OVB). Three hundred and thirty women aged 15-49, non-pregnant, non-breastfeeding who were referred to gynecologic clinics were surveyed. A questionnaire was used to collect data. Women with no symptoms related to urinary incontinence (UI) and OVB served as the reference group. The risk of all types of UI and OVB increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
3
20
0
2
Order By: Relevance
“…These results corroborate those found by Herrmann et al 25 , who reported cure or improvement in 81.7% of the women with UI following treatment. Other authors reported a cure rate of 84% in women with different types of UI after training the pelvic floor 18,21 . Therefore, the success rate in the present study falls within the success rate ranges described in the international literature, despite the lower frequency and shorter duration of treatment sessions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These results corroborate those found by Herrmann et al 25 , who reported cure or improvement in 81.7% of the women with UI following treatment. Other authors reported a cure rate of 84% in women with different types of UI after training the pelvic floor 18,21 . Therefore, the success rate in the present study falls within the success rate ranges described in the international literature, despite the lower frequency and shorter duration of treatment sessions.…”
Section: Discussionmentioning
confidence: 96%
“…Constipation may stimulate bladder receptors, which may reduce its contractility and cause incomplete bladder emptying, a common complaint among women with UI 8 . Therefore, the importance of treating constipation alongside the treatment for UI is clear because the risk for all types of UI increases with constipation 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by Sobhgol and Charandabee 24 indicate that the risk for all types of UI increased with constipation 24 . In the present study, more than one third of the participants (37.5%) reported constipation.…”
Section: Discussionmentioning
confidence: 89%
“…Vaginal delivery was considered prognostic of all three types of incontinence 24 . In this study, there was a predominance of MUI among the participants who had normal delivery, while those who have been submitted to cesarean section had significant association with the diagnosis of SUI.…”
Section: Discussionmentioning
confidence: 99%
“…Miedel et al [18] found that OAB symptoms were related to anterior and posterior compartment prolapse but not to the central compartment. On the other hand, Sobhgol and Charandabee [19] reported that OAB symptoms weakened and urge incontinence worsened as prolapse grade increased in all compartments. However, other studies observed that women with a higher grade of bladder descent were less likely to suffer from urge incontinence, perhaps because bladder displacement prevented leakage [11,20,21] .…”
Section: Discussionmentioning
confidence: 99%